Perceived Cause and Effect Relationship for Nutritional Anemia Among Adolescent Girls in Rural Puducherry - Mayura S; Suguna E; Dongre AR (Online Journal of Health & Allied Sciences, 2014)
Background & Objectives: The prevalence of nutritional anemia among adolescent girls is high (47.6% to 90%) as previously reported in the different parts of North India. Since there are limited studies on nutritional anemia at the sub-district level in the Southern part of India, there is a need to know the extent of the problem among adolescent girls to plan context specific interventions. With this background, the present study was done with the objectives 1) To find the prevalence of nutritional anemia among adolescent girls 2) To ‘qualitatively’ explore their perceptions of the causes and effects of nutritional anemia. Methods: The study was undertaken in two wards of Kallitheerthalkuppam village, the field practice area of the Department of Community Medicine, SMVMCH, Puducherry. Mixed-methods design which includes quantitative (survey) and qualitative (cause-effect diagram) methods was used. A representative sample of 100 adolescent girls aged 12-19 years were the study participants. Data for quantitative (survey using a questionnaire) and qualitative (cause-effect diagram) methods were collected over the period of two months. Result: The prevalence of anemia among the study population was 58 per cent. In The cause and effect diagram exercise, girls linked deficiency of iron as the cause for tiredness, irregular menstrual cycles and low birth weight. They also linked deficiency of iron and the habit of not wearing footwear to tiredness, reduced intake of green leafy vegetables, and intestinal worm infections to giddiness and hookworm infections to peptic ulcer. Interpretation & Conclusions: The study found a gap between knowledge and practice as reflected in the cause and effect diagram. This result indicates the need to initiate an effective behavior change communication for improving the hemoglobin status of adolescent girls.